2010
DOI: 10.1111/j.1365-2141.2010.08191.x
|View full text |Cite
|
Sign up to set email alerts
|

Modern management of severe platelet function disorders

Abstract: SummarySevere platelet function defects are rare disorders that require expertise in diagnosis and management. Therefore patients with such disorders should be referred to and managed in centres with the full laboratory repertoire of tests and clinical support necessary to optimise their quality of care. The aim of this review is to discuss the management of these patients in various clinical situations including surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 94 publications
1
115
0
3
Order By: Relevance
“…It has been reported that anti-fibrinolytics [19], the recombinant factor VIIa [20], and vasopressin [21], which stimulates the release of factor VII, may be useful for treatment of severe bleedings in patients with BSS. Although platelet transfusion was omitted, these regents may also support the hemostasis [22]. In addition, to the best of our knowledge, this is the first case to be treated with cytotoxic chemotherapy for malignant tumor with BSS.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that anti-fibrinolytics [19], the recombinant factor VIIa [20], and vasopressin [21], which stimulates the release of factor VII, may be useful for treatment of severe bleedings in patients with BSS. Although platelet transfusion was omitted, these regents may also support the hemostasis [22]. In addition, to the best of our knowledge, this is the first case to be treated with cytotoxic chemotherapy for malignant tumor with BSS.…”
Section: Discussionmentioning
confidence: 88%
“…Bone marrow transplantation is the treatment to cure the disorder, although it has only been performed in a few cases with clinically severe phenotype [41].…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…In both of these disorders, significant mucocutaneous bleeding and ICH have been reported, although ICH is rare, occurring in only 0.3% to 2.0% of patients with GT and even less in those with BSS. 103,104 The PFA-100 is a fairly reliable screening mechanism for these diagnoses (Table 1). 102,103 Less well characterized but more common, the disorders of platelet signaling and secretion result from a variety of defects.…”
Section: Congenital Platelet Abnormalitiesmentioning
confidence: 99%
“…103,104 The PFA-100 is a fairly reliable screening mechanism for these diagnoses (Table 1). 102,103 Less well characterized but more common, the disorders of platelet signaling and secretion result from a variety of defects. Platelet activation leads to a conformational change in the platelet and normally results in secretion of platelet granule contents, which recruits other platelets to the site of injury.…”
Section: Congenital Platelet Abnormalitiesmentioning
confidence: 99%